Modeling and parametric study of a force-amplified compressive-mode piezoelectric energy harvester. (February 2017) - Yang, Zhengbao; Zu, Jean; Luo, Jun; Peng, Yan
Piezoelectric energy harvesters have great potential for achieving inexhaustible power supply for small-scale electronic devices. However, the insufficient power-generation capability and the narrow working bandwidth of traditional energy harvesters have significantly hindered their adoption. To address these issues, we propose a nonlinear compressive-mode piezoelectric energy harvester. We embedded a multi-stage force amplification mechanism into the energy harvester, which greatly improved its power-generation capability. In this article, we describe how we first established an analytical model to study the force amplification effect. A lumped-parameter model was then built to simulate the strong nonlinear responses of the proposed energy harvester. A prototype was fabricated which demonstrated a superior power output of 30 mW under an excitation of 0.3 g (g = 9 . 8 m/s 2 ). We discuss at the end the effect of geometric parameters that are influential to the performance. The proposed energy harvester is suitable to be used in low-frequency weak-excitation environments for powering wireless sensors.